2013
DOI: 10.1007/s00284-013-0380-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection

Abstract: Although intestinal flora are crucial in maintaining immune homeostasis of the intestine, the role of intestinal flora in immune responses at other mucosal surfaces remains less clear. Here, we show that intestinal flora composition critically regulates the toll-like receptor 7 (TLR7) signaling pathway following respiratory influenza virus infection. TLR7 ligands rescued the immune impairment in antibiotic-treated mice. Intact microbiota provided signals leading to the expression of mRNA for TLR7, MyD88, IRAK4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 29 publications
3
90
0
1
Order By: Relevance
“…The GIT microbiota plays an important role in the induction and regulation of host responses to various pathogens including bacteria 1214 , fungi 15 and viruses 1618 . Recently, we showed that changes in the composition of the gut microbiota towards a dysbiotic condition resulted in higher oropharyngeal and cloacal shedding of AIV subtype H9N2 in chickens, which was also associated with compromised type I interferon (IFN) expression 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The GIT microbiota plays an important role in the induction and regulation of host responses to various pathogens including bacteria 1214 , fungi 15 and viruses 1618 . Recently, we showed that changes in the composition of the gut microbiota towards a dysbiotic condition resulted in higher oropharyngeal and cloacal shedding of AIV subtype H9N2 in chickens, which was also associated with compromised type I interferon (IFN) expression 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the immune response to chronic antigenic stimulation or dysregulation of the immune response could be associated with increased disease risk [49] and both of those scenarios could involve the microbiota, as the microbiota is the primary antigenic exposure in the oral cavity and is known to closely interact with the immune system at other body sites [50,51]. Overgrowth of opportunistic pathogens residing in the oral cavity because of advanced immunocompromise is another potential cause.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that germfree mice were more susceptible to Klebsiella pneumoniae pneumonia and that priming germfree mice with lipopolysaccharide (LPS) or other TLR agonists increased their inflammatory responsiveness and led to better bacterial clearance and mouse survival (28). Two studies recently demonstrated that the GI tract microbiota also regulates immune defenses in the respiratory tract against influenza virus infection via the TLR7 pathway (29) or inflammasome activation (30). Gut microbiota are likely important not only in infections in the lung, as microbiota modulate tumoral immune surveillance in this tissue via the Th17 pathway as well (31).…”
Section: Discussionmentioning
confidence: 99%